1974
DOI: 10.1267/ahc.7.217
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Demonstration of Nonspecific Esterases in the Small Intestine of the Rat

Abstract: The nonspecific esterase activity was investigated at the electron microscopic level, by means of azo dye technique applied to the duodenal, jejunal and ileal mucosae of living rats. After perfusion of a medium containing 1-naphthyl acetate and hexazonium pararosaniline into the lumen of the small intestine, the enzyme reaction product of electron opaque grains (50-100 nm in diameter) was localized on the limiting membrane of microvilli of epithelial cells, and on the vesicles and the granular endoplasmic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although its specificity is somewhat less than other substrates such as 5-bromoindoxyl acetate (2) and naphthyl acetate (18), the reaction occurs directly and in a single step. Wachstein et al (17) have demonstrated with light microscopy that the distribution patterns of esterase detected with thiolacetic acid were comparable to those of napthhol-AS and 5-bromoindoxyl acetate substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Although its specificity is somewhat less than other substrates such as 5-bromoindoxyl acetate (2) and naphthyl acetate (18), the reaction occurs directly and in a single step. Wachstein et al (17) have demonstrated with light microscopy that the distribution patterns of esterase detected with thiolacetic acid were comparable to those of napthhol-AS and 5-bromoindoxyl acetate substrates.…”
Section: Discussionmentioning
confidence: 99%